Populasi dan Intensitas Serangan Larva Spodoptera litura F. pada Tanaman Sawi Hijau (Brassica juncea L.) - Rafu, Herminda; Atini, Blasius; Santiari, Made (Journal Science of Biodiversity, 2023)
Green mustard farmers in the Beba area experienced a decrease in crop yields due to attacks by armyworm larvae. A study needs to be conducted to determine the average population and intensity of the attack by larvae of S. litura F. on mustard greens aged 6 DAP, 8 DAP, 10 DAP, and 12 DAP in the determined plots. The study was conducted in the Beba area, Oelami Village, South Bikomi District, from December 2021 to January 2022. The total observation sub-plots were 16 and the size of each sub-plot is 60 x 60 cm. The collection of S. litura F. and attack intensity observation were carried out starting from 6 DAP – 12 DAP at 06.00-08.00 am. The mean population of S. litura F. larvae obtained from mustard greens aged 6 DAP; 8 DAP, 10 DAP, and 12 DAP was respectively 0.029 DAP/clump; 0.154 head/clump, 0.632 head/clump, and 0.688 head/clump. The percentage of attack intensity on plants aged 6 DAP, 8 DAP, 10 DAP, and 12 DAP were respectively 0.041%; 0.097%; 0.23%, and 0.246%. The attack intensity category is still in the mild category. The highest average population of S. litura F. larvae and the highest percentage of attack intensity was at the age of 12 DAP.